Cultivating Tolerance in East Priangan: Religious Moderation in the Eastern Universities of West Java, Indonesia - Ainissyifa, Hilda; Nabhani, Irfan; Nasrullah, Yufi Mohammad; Fatonah, Nurul; Nazib, Fiqra Muhamad (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2024)
Religious moderation has become increasingly relevant in diverse and pluralistic societies, particularly within academic settings where varying interpretations of religious teachings often emerge. This study highlights the growing need to explore and understand religious attitudes among students in the context of their social, cultural, and political influences. The study investigates students' perceptions and views regarding religious moderation by delving into critical issues such as the relationship between Pancasila and religion, the idea of a caliphate state, respect for state symbols, and attitudes toward violence. A quantitative survey approach involved 463 students selected through stratified random sampling from various study programs and semester levels. Data were collected using a structured questionnaire to assess students' perspectives on these controversial topics. The findings reveal a comprehensive picture of religious attitudes among students, emphasizing the importance of fostering religious moderation within academic environments. These results underline the necessity for effective educational strategies to promote understanding and respect for diverse beliefs while minimizing conflict. The study is significant for policymakers, educators, and practitioners because it offers insights into the dynamics of religious attitudes in higher education. Addressing religious moderation's complexities, these findings contribute to developing strategies that can support harmonious coexistence in pluralistic academic communities.